Molten fatty acid based microemulsions. Issue 23 (31st May 2016) - Noirjean, Cecile; Testard, Fabienne; Dejugnat, Christophe; Jestin, Jacques; Carriere, David
Abstract : We show that ternary mixtures of water (polar phase), myristic acid (MA, apolar phase) and cetyltrimethylammonium bromide (CTAB, cationic surfactant) studied above the melting point of myristic acid allow the preparation of microemulsions without adding a salt or a co-surfactant. Abstract : We show that ternary mixtures of water (polar phase), myristic acid (MA, apolar phase) and cetyltrimethylammonium bromide (CTAB, cationic surfactant) studied above the melting point of myristic acid allow the preparation of microemulsions without adding a salt or a co-surfactant. The combination of SANS, SAXS/WAXS, DSC, and phase diagram determination allows a complete characterization of the structures and interactions between components in the molten fatty acid based microemulsions. For the different structures characterized (microemulsion, lamellar or hexagonal phases), a similar thermal behaviour is observed for all ternary MA/CTAB/water monophasic samples and for binary MA/CTAB mixtures without water: crystalline myristic acid melts at 52 °C, and a thermal transition at 70 °C is assigned to the breaking of hydrogen bounds inside the mixed myristic acid/CTAB complex (being the surfactant film in the ternary system). Water determines the film curvature, hence the structures observed at high temperature, but does not influence the thermal behaviour of the ternary system. Myristic acid is partitioned in two "species" that behave independently: pure myristic acid and myristic acid associated with CTAB to form an equimolar complex that plays the role of the surfactant film. We therefore show that myristic acid plays the role of a solvent (oil) and a co-surfactant allowing the fine tuning of the structure of oil and water mixtures. This solvosurfactant behaviour of long chain fatty acid opens the way for new formulations with a complex structure without the addition of any extra compound.